Short Scar Male Neck Lift: A Minimally Invasive Option for Neck Contouring - Somenek, Michael T. (Facial Plastic Surgery, 2025)
While facelift literature has largely focused on female patients, recent research highlights unique anatomical and psychosocial considerations in male facial rejuvenation. The short scar neck lift is explored to present the indications, technique, and outcomes as an alternative to the deep plane facelift in selected male patients.The short scar neck lift employs limited periauricular incisions to address submental fullness, platysmal banding, and mild-to-moderate cervical skin laxity. Ideal candidates demonstrate localized cervical and mandibular aging without significant midface descent. The procedure may be combined with submental liposuction, platysmaplasty, and energy-based devices to enhance skin contraction.In appropriately selected patients, the short scar neck lift achieves meaningful improvement in cervicomental angle definition with reduced operative time, morbidity, and recovery compared with deep plane facelifts. The short scar neck lift is a versatile, lower-morbidity alternative for male patients with localized cervical aging. Its targeted approach, adaptability, and favorable recovery profile make it a valuable addition to the male facial rejuvenation surgical algorithm.
Keywords: neck lift; radiofrequency; jawline; skin tightening